2015
DOI: 10.1590/2177-6709.20.6.043-051.oar
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric norms and esthetic profile preference for the Japanese: a systematic review

Abstract: Objective: To determine the cephalometric parameters and esthetic preferences of a pleasant face for the Japanese population. Methods: For the present study, the following databases were accessed: PubMed, Embase, Scopus and Web of Science. Initial inclusion criteria comprised studies written in English and quoting cephalometric norms and/or facial attractiveness in Japanese adults. No time period of publication was determined. The quality features evaluated were sample description, variables analyzed and how c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 16 publications
0
21
0
3
Order By: Relevance
“…Younger people have larger lips than older. Lower lip thickness highest percentage if correct for age Three-dimensional technology used for morphological and metrical analysis Penna et al [ 24 ] 2015 176 Lip morphology Cross-sectional level IV High ratio of upper vermillion height to mouth–nose distance and chin–nose distance in and wider vermillion height/chin–mouth distance in attractive females 250 voluntary judges through an Internet presentation Wu et al [ 25 ] 2015 80 patients 50 landmarks Facial characteristics Case control level III Attractive men had large forehead reduced mandible round baby face characteristics Consider individual faces—Chinese population Farrera et al [ 26 ] 2015 565 patients Asymmetry Cross-sectional level IV Attractiveness and asymmetry are not correlated Use two-dimensional digital photographs and geometric morphometric methods Mexican population Bronfman et al [ 41 ] 2015 13 studies Facial distances, angles and features Systematic review of level III trials level III Japanese adults have less bilabial protrusion, less prominent nose. Japanese adults prefer a more retruded profile Used some skeletal measurements Hwang et al [ 19 ] 2015 37 Eye measurements Cross-sectional level IV Beautiful women and femme fatales have same inter-pupillary distance Western society Hwang et al [ 27 ] 2014 31 43 distances and angles in young and old Leonardo’s profile drawings Cross-sectional level IV …”
Section: Resultsmentioning
confidence: 99%
“…Younger people have larger lips than older. Lower lip thickness highest percentage if correct for age Three-dimensional technology used for morphological and metrical analysis Penna et al [ 24 ] 2015 176 Lip morphology Cross-sectional level IV High ratio of upper vermillion height to mouth–nose distance and chin–nose distance in and wider vermillion height/chin–mouth distance in attractive females 250 voluntary judges through an Internet presentation Wu et al [ 25 ] 2015 80 patients 50 landmarks Facial characteristics Case control level III Attractive men had large forehead reduced mandible round baby face characteristics Consider individual faces—Chinese population Farrera et al [ 26 ] 2015 565 patients Asymmetry Cross-sectional level IV Attractiveness and asymmetry are not correlated Use two-dimensional digital photographs and geometric morphometric methods Mexican population Bronfman et al [ 41 ] 2015 13 studies Facial distances, angles and features Systematic review of level III trials level III Japanese adults have less bilabial protrusion, less prominent nose. Japanese adults prefer a more retruded profile Used some skeletal measurements Hwang et al [ 19 ] 2015 37 Eye measurements Cross-sectional level IV Beautiful women and femme fatales have same inter-pupillary distance Western society Hwang et al [ 27 ] 2014 31 43 distances and angles in young and old Leonardo’s profile drawings Cross-sectional level IV …”
Section: Resultsmentioning
confidence: 99%
“… 32 Demands for the improvement in dental aesthetics are generally increasing, although there are differences in what is considered attractive and desirable because of different, cultural, ethnic, socioeconomic factors. 33 34 35 Orthodontic treatment, especially fixed appliances, has side effects and potential complications. 36 37 38 39 Therefore, it is necessary to work to raise awareness of the importance of functional occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Even though cephalometric values are still used as a normality reference in orthodontics, it is known that variability can occur from each patient, for many different reasons. Innumerous studies have shown that cephalometric numbers differ according to race, genetics backgrounds or orofacial anomalies …”
Section: Introductionmentioning
confidence: 99%